Giraffe reflections - Peterson, Dale (University of California Press, 2013)
"...this volume presents a magnificent portrait of a group of animals who, in spite of their legendary elegance and astonishing gentleness, may not entirely survive this century. Dale Peterson's text provides a natural and cultural history of the world's tallest and second-biggest land animals, describing in detail their biology and behavior. He offers a new perspective on the giraffes' place in our world, and argues for the stronger protection of these imposing yet endangered creatures and their elusive forest relatives, the okapis. Some 120 stunning photographs by award-winning wildlife photographer Karl Ammann capture the grace and elegance of Giraffa camelopardalis. Both beautiful and informative, the images document giraffes' complex interactions with each other and their environment"--Provided by the publisher.